Survey about the microbiological features, the oenological performance and the influence on the character of wine of active dry yeast employed as starters of wine fermentation. (14th July 2014) - Guzzon, Raffaele; Nicolini, Giorgio; Nardin, Tiziana; Malacarne, Mario; Larcher, Roberto
<x xml:space="preserve">Abstract</x> In this work we compared the microbiological features and the fermentative aptitude of 29 different ADY available on the Italian market. Each sample was essayed by microbiological analysis and fermentations in 3 different grape musts. Attention was focused on the presence of wine spoilage microorganisms inside ADY, and on the degradation/production of secondary metabolites having a relevant impact on the quality of wine. <boxed-text content-type="graphic" id="ijfs12610-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>